The Effectiveness of Task-Based Language Teaching in Developing Speaking Skills at SMKN 2 MALANG - Tities Hijratur Rahmah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
In this study the researcher proposed using a procedure based on the use of tasks as the core unit of planning and instruction in language teaching called Task-Based language Teaching (TBLT) to enhance the speaking ability of EFL learners. The present study was focused on seeing whether the TaskBased Language Teaching more effective to develop the students’ achievement in speaking. In this study the researcher used the population of the tenth grade students of SMKN 2 Malang in 20014/20015 academic year. In conducting this research, the researcher used the quasi-experimental design in terms of using one experimental group and one control group. These groups were chosen randomly from tenth grade classes from the two classes. The result of this study shows that there is a signifcant difference in the scores for Task- Based Language Teaching method and Audio lingual method after controlling for scores on the test. From the ANCOVA computation, it can be concluded that the students in experimental group had better achievement than those in control group.